2020
DOI: 10.1136/bmjspcare-2020-002410
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unscheduled care use by cancer decedents: a systematic review with narrative synthesis

Abstract: BackgroundPeople who die from cancer (cancer decedents) may experience unpleasant and distressing symptoms which cause them to present to unscheduled care. Unscheduled care is unplanned care delivered by general practitioner out-of-hours and emergency departments. Use of unscheduled care can disrupt treatment plans, leading to a disjointed patient care and suboptimal outcomes.ObjectivesThis systematic review aimed to identify factors associated with unscheduled care use by cancer decedents.MethodSystematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Several authors have shown the usefulness of a nurse specialist in PC in the ES, or that the collaboration between the emergency department and PC was positive, as we mentioned above would improve health care. Likewise, the widespread complaint was for lack of time, overload, lack of training or inadequate training with respect to the scope of PC [31,32]. In fact, some authors say that respiratory and gastrointestinal oncological processes can be well managed without using emergency units [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown the usefulness of a nurse specialist in PC in the ES, or that the collaboration between the emergency department and PC was positive, as we mentioned above would improve health care. Likewise, the widespread complaint was for lack of time, overload, lack of training or inadequate training with respect to the scope of PC [31,32]. In fact, some authors say that respiratory and gastrointestinal oncological processes can be well managed without using emergency units [33].…”
Section: Discussionmentioning
confidence: 99%
“…Unscheduled care research has focussed previously on emergency department attendance and people with cancer. [27][28][29] This study included all NHS unscheduled healthcare services and people who died from any underlying cause. Cohort studies using large administrative datasets are being used increasingly to measure healthcare systems outcomes and screen populations with serious illness for palliative care and care planning.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…People dying from cancer frequently attend the General Practice Out-of-Hours (GPOOH) service in their last year of life [13][14][15][16] . However, all large-scale research into unscheduled care in the UK has relied on routine healthcare datasets 13,15 , which only contain coded data.…”
Section: Introductionmentioning
confidence: 99%
“…People dying from cancer frequently attend the General Practice Out-of-Hours (GPOOH) service in their last year of life [13][14][15][16] . However, all large-scale research into unscheduled care in the UK has relied on routine healthcare datasets 13,15 , which only contain coded data. Data coding is the process by which medical, social, prescribing, and other routinely-collected clinical information are recorded in a set of pre-determined categories.…”
Section: Introductionmentioning
confidence: 99%